Paying for Performance in Public Pension Plans - Lu, Yan; Mullally, Kevin; Ray, Sugata (Management Science, 2023)
We examine the relation between public pension plan chief investment officer (CIO) compensation and plans’ investment performance. Higher paid CIOs outperform their counterparts by 47–60 basis points per year, largely through increased and superior investment in private equity and real estate. This outperformance generates an additional 74.91–95.63 million in economic value. Plans offering higher compensation hire better educated CIOs and are more likely to retain their CIOs. Higher CIO compensation is positively correlated with the use of incentive compensation, but incentive compensation does not directly affect performance. Demand- and supply-side frictions help explain the variation in CIO pay and the persistent low compensation paid by some plans despite the positive relation between compensation and performance. This paper was accepted by Victoria Ivashina, finance. Funding: S. Ray gratefully acknowledges a summer research grant from the Culverhouse College of Business at the University of Alabama. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2022.4554 .